Inhibition of 14q32 microRNA miR-495 reduces lesion formation, intimal hyperplasia and plasma cholesterol levels in experimental restenosis - Welten, Sabine M.J.; de Jong, Rob C.M.; Wezel, Anouk; de Vries, Margreet R.; Boonstra, Martin C.; Parma, Laura; Jukema, J. Wouter; van der Sluis, Tetje C.; Arens, Ramon; Bot, Ilze; Agrawal, Sudhir; Quax, Paul H.A.; et al. (Atherosclerosis, 2017)
We aimed at investigating the role of 14q32 microRNAs in intimal hyperplasia and accelerated atherosclerosis; two major contributors to restenosis. Restenosis occurs regularly in patients treated for coronary artery disease and peripheral arterial disease. We have previously shown that inhibition of 14q32 microRNAs leads to increased post-ischemic neovascularization, and microRNA miR-494 also decreased atherosclerosis, while increasing plaque stability. We hypothesized that 14q32 microRNA inhibition has beneficial effects on intimal hyperplasia, as well as accelerated atherosclerosis. Non-constrictive cuffs were placed around both femoral arteries of C57BL/6J mice to induce intimal hyperplasia. Accelerated atherosclerotic plaque formation was induced in hypercholesterolemic ApoE−/− mice by placing semi-constrictive collars around both carotid arteries. 14q32 microRNAs miR-329, miR-494 and miR-495 were inhibited in vivo using Gene Silencing Oligonucleotides (GSOs). GSO-495 administration led to a 32% reduction of intimal hyperplasia. Moreover, the number of macrophages in the arterial wall of mice treated with GSO-495 was reduced by 55%. Inhibition of miR-329 and miR-494 had less profound effects on intimal hyperplasia. GSO-495 administration also decreased atherosclerotic plaque formation by 52% and plaques of GSO-495 treated animals showed a more stable phenotype. Finally, cholesterol levels were also decreased in GSO-495 treated animals, via reduction of the VLDL-fraction. GSO-495 administration decreased our primary outcomes, namely intimal hyperplasia, and accelerated atherosclerosis. GSO-495 administration also favourably affected multiple secondary outcomes, including macrophage influx, plaque stability and total plasma cholesterol levels. We conclude that 14q32 microRNA miR-495 is a promising target for prevention of restenosis. [Display omitted] •Inhibition of 14q32 microRNA miR-495 reduces intimal hyperplasia.•Inhibition of miR-495 decreases accelerated atherosclerosis.•Inhibition of miR-495 increases plaque stability.•Inhibition of miR-495 decreases plasma cholesterol levels.•Overall, inhibition of miR-495 reduces post-interventional restenosis.